GERMINATION RESPONSE OF ZANTHOXYLUM CAPENSE (SMALL KNOBWOOD) SEEDS TO DIFFERENT PRE-TREATMENT PROTOCOLS - Bodede, Olusola; Shaik, Shakira; Moodeley, Roshilla (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
In this work, the germination of Zanthoxylum capense seeds, in response to various scarification and stratification treatments, was studied. The highest final germination percentage (FGP) (71.1%) was obtained from seeds soaked in hot water for 15 minutes and grown in dark conditions. The 30 days chilling treatment also gave a good response (57.8%) when grown under light or dark conditions. Other FGPs of note included seeds soaked with 500 ppm gibberellic acid (GA3) (60%, light; 44.4%, dark) and 1000 ppm GA3 (46.7%, light; 48.9%, dark) and soaking in H2SO4 for 5 minutes (42.2%, dark). Overall, the seeds sown under dark conditions produced better FGPs than those sown in light. These results reveal that Z. capense seeds display combinational dormancy, that imposed physically by the seed coat and that imposed physiologically by the embryo. These dormancy traits can be easily overcome by either chilling or soaking in hot water or GA3.